The Effective Improvement of Socialization and Assistance of Physical Sport and Health Education (PSHE) Teacher Working Group (MGMP) at Senior High School Level in North Central Timor (Journal of Physical Education and Sports, 2019)
This study aims to analyze the improvement of the effectiveness of the Physical Sport and Health Education (PSHE) Teachers Working Group (MGMP) in Senior High School of all districts in North Central Timor through socialization and assistance. The research method applied a qualitative approach with single-case design. Techniques for collecting the data were through observation, interviews, and documentation. The subjects of the study were the chairman of MGMP, the committee of MGMP and PSHE teachers. There were several techniques used to analyze the data, such as (1) data reduction, (2) data presentation, and (3) conclusion/verification. The result showed that: (a) The early condition of MGMP described a lack of information and communication, (b) the first socialization showed that the participants understand the goals and functions of MGMP, (c) the second socialization was the planning of work program namely the monthly, semester and annual program, (d) the third socialization was the equalization of the lesson plan and syllabus in MGMP 2019 for senior high school in North Central Timor. It can be concluded that there was an improvement in the effectiveness of PSHE MGMP through socialization stage one until three. After the socialization has been done, the study was a success because one of the programs from PSHE MGMP, namely the equalization of the lesson plan and syllabus in senior high school level could run smoothly. Therefore, the researcher suggested better supervision from School Supervisor Coordinator (KORWAS) and District PPO Service, and also the program from MGMP should be supported by the headmaster and teacher.